Greatly increased prevalence of esophageal dysmotility observed in persons with spinal cord injury. Issue 7 (16th September 2014) - Radulovic, M.; Schilero, G. J.; Yen, C.; Bauman, W. A.; Wecht, J. M.; Ivan, A.; La Fountaine, M. F.; Korsten, M. A.
Summary The effects of spinal cord injury (SCI) on esophageal motility are largely unknown. Furthermore, due to the complete or partial loss of sensory innervation to the upper gastrointestinal tract, a symptom‐based diagnosis of esophageal dysmotility is problematic in the SCI population. To determine the prevalence and characterize the type of motility disorders observed in persons with chronic SCI compared with that of able‐bodied (AB) controls based on esophageal pressure topography isometrics acquired by high‐resolution manometry and categorized by application of the Chicago Classification. High‐resolution manometry of the esophagus was performed in 39 individuals: 14 AB, 12 with paraplegia (level of injury between T4–T12) and 13 with tetraplegia (level of injury between C5–C7). A catheter containing multiple pressure sensors arranged at 360° was introduced into the esophagi of subjects at a distance that allowed visualization of both the upper esophageal sphincters (UES) and lower esophageal sphincters (LES). After a period to acquire pressures at baseline, subjects were asked to perform 10 wet swallows with 5‐mL boluses of isotonic saline while esophageal pressure and impedance were being recorded. No significant differences were noted for gender, age, or body mass index between AB and SCI groups. Twenty‐one of 25 (84%) subjects with SCI had at least one motility abnormality: 12% with Type II achalasia, 4% with Type III achalasia, 20% with esophagogastric junction outflow obstruction, 4% with the hypercontractile esophagus, and 48% with peristaltic abnormalities (weak peristalsis with small or large defects or frequent failed peristalsis). In contrast, only 7% (1 out of 14) of the AB subjects had any type of esophageal motility disorder. Despite the lack of subjective complaints and clinical awareness, esophageal dysmotility appears to be a highly prevalent condition in persons with SCI. The use of new and improved techniques, as well as a more stringent classification system, permitted the identification of the presence of nonspecific motility disorders in almost all SCI subjects, including four individuals who were previously undiagnosed with achalasia. Future work in persons with SCI is required to clarify the clinical impact of this observation and to study potential associations between esophageal dysmotility, gastroesophageal reflux disease, and pulmonary function. An increased awareness of esophageal dysfunction in the SCI population may lead to the development of new clinical guidelines for the diagnosis, prevention, and treatment of these largely unrecognized disorders.